Sistem Pelayanan Berbasis Web Pada Wedding Organizer Putri Hanastari - Ferdiana Kartika Putri; Novita Mariana (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
A wedding organizer is a service intended to help someone realize their dream wedding from planning to execution. Princess Hanastari's wedding organizer is a wedding service in Grobogan Regency, which provides various types of wedding packages, the ordering process for Putri Hanastari is still manual via WhatsApp and comes directly to Putri Hanastari's place. Therefore it will have an impact on the duration of time for consumers to get schedules, price information, and facilities offered by the owner. To prevent this, it is necessary to build a web-based service system for wedding organizers. The system built uses the PHP Mysql programming language, the waterfall method and the FCFS (First Come First Serve) scheduling algorithm and uses blackbox testing. The creation of a web-based service system for wedding organizers is expected to be able to maximize services so that they are effective and efficient in disseminating the information offered and making it easier for consumers to order wedding packages.